Experimental investigations on the explosivity of steam‐driven eruptions: A case study of Solfatara volcano (Campi Flegrei). Issue 11 (25th November 2016) - Montanaro, Cristian; Scheu, Bettina; Mayer, Klaus; Orsi, Giovanni; Moretti, Roberto; Isaia, Roberto; Dingwell, Donald B.
Abstract: Steam‐driven eruptions, both phreatic and hydrothermal, expel exclusively fragments of non‐juvenile rocks disintegrated by the expansion of water as liquid or gas phase. As their violence is related to the magnitude of the decompression work that can be performed by fluid expansion, these eruptions may occur with variable degrees of explosivity. In this study we investigate the influence of liquid fraction and rock petrophysical properties on the steam‐driven explosive energy. A series of fine‐grained heterogeneous tuffs from the Campi Flegrei caldera were investigated for their petrophysical properties. The rapid depressurization of various amounts of liquid water within the rock pore space can yield highly variable fragmentation and ejection behaviors for the investigated tuffs. Our results suggest that the pore liquid fraction controls the stored explosive energy with an increasing liquid fraction within the pore space increasing the explosive energy. Overall, the energy released by steam flashing can be estimated to be 1 order of magnitude higher than for simple (Argon) gas expansion and may produce a higher amount of fine material even under partially saturated conditions. The energy surplus in the presence of steam flashing leads to a faster fragmentation with respect to gas expansion and to higher ejection velocities imparted to the fragmented particles. Moreover, weak and low permeability rocks yield a maximum fine fraction. Using experiments to unravel the energetics of steam‐driven eruptions has yielded estimates for several parameters controlling their explosivity. These findings should be considered for both modeling and evaluation of the hazards associated with steam‐driven eruptions. Key Points: Experimental studies to unravel the steam‐driven eruption energetics Influence of liquid fraction and rock petrophysical properties on the explosive energy Steam flashing results in a faster fragmentation with respect to gas expansion and into higher ejection velocities of fragmented material